2021
DOI: 10.7554/elife.64930
|View full text |Cite
|
Sign up to set email alerts
|

SAM homeostasis is regulated by CFIm-mediated splicing of MAT2A

Abstract: S-adenosylmethionine (SAM) is the methyl donor for nearly all cellular methylation events. Cells regulate intracellular SAM levels through intron detention of MAT2A, the only SAM synthetase expressed in most cells. The N6-adenosine methyltransferase METTL16 promotes splicing of the MAT2A detained intron by an unknown mechanism. Using an unbiased CRISPR knock-out screen, we identified CFIm25 (NUDT21) as a regulator of MAT2A intron detention and intracellular SAM levels. CFIm25 is a component of the cleavage fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 112 publications
(188 reference statements)
2
22
0
Order By: Relevance
“…43 Intriguingly, CFI m is also implicated in regulating SAM homeostasis in concordance with METTL16. 36 It is hypothesized that METTL16 acts as a SAM sensor that facilitates CFI m -mediated splicing of Mat2A mRNA. The differences in SAM concentrations in the cell that have been reported when Mat2B activity is knocked out could therefore be caused by its interaction with CFI m , which in turn affects the amount of Mat2A being synthesized via mRNA splicing.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…43 Intriguingly, CFI m is also implicated in regulating SAM homeostasis in concordance with METTL16. 36 It is hypothesized that METTL16 acts as a SAM sensor that facilitates CFI m -mediated splicing of Mat2A mRNA. The differences in SAM concentrations in the cell that have been reported when Mat2B activity is knocked out could therefore be caused by its interaction with CFI m , which in turn affects the amount of Mat2A being synthesized via mRNA splicing.…”
Section: ■ Resultsmentioning
confidence: 99%
“…It would be important to measure the absolute concentration of Mat2A (and Mat2B) in different cell types under different physiological conditions to determine if the in vitro rate of Mat2A is fast enough to maintain the metabolic supply of SAM. Recently, the RNA binding protein and methyltransferase METTL16 have been implicated in regulating cellular Mat2A concentrations in response to the levels of SAM. When SAM concentrations are high, METTL16, which utilizes SAM as a substrate, binds and methylates Mat2A mRNA resulting in intron retention and degradation, which cause a reduction in the cellular concentrations of the Mat2A protein and SAM . When cellular SAM concentrations are low, the methylation of Mat2A mRNA by METTL16 is reduced, resulting in increased levels of Mat2A mRNA being translated into the Mat2A protein and an increase in the cellular SAM concentration. Therefore, METTL16 acts as a SAM sensor that directly regulates the amount of Mat2A enzyme in the cell in response to cellular SAM concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the sites of m 6 A on MAT2A pre-mRNA are occupied, METTL16 is quickly separated from MAT2A pre-mRNA, increases retention of the last intron in MAT2A pre-mRNA, and reduces its stability. However, in SAM-limiting conditions, METTL16 binds to unmethylated MAT2A pre-mRNA to promote the splicing of MAT2A pre-mRNA by recruiting the cleavage factor I m complex (CFIm), and finally increases the expression of MAT2A mature mRNA ( Scarborough et al, 2021 ). In brief, the effects of METTL3 and METTL16 likely reflect the typical “Writer—Reader” paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Similar assays in other cell types are imperative to validate these findings and unravel the precise underlying molecular mechanisms. Secondly, previous studies have shown that CFIm25 can regulate global mRNA alternative polyadenylation (APA) in many cell types [ 30 , 31 , 37 , 39 , 41–43 , 45 , 46 ], while recent reports demonstrated that it could also regulate mRNA splicing in specific genes [ 72 , 73 ]. Future explorations are expected to reveal whether they are associated with CFIm25ʹs potential role in transcriptional regulation, and to elucidate mechanisms underlying coordination of these multiple regulatory roles.…”
Section: Discussionmentioning
confidence: 99%